Analysis of Class VII Students' Learning Motivation at SMPN 13 Bontoa, Maros Regency in Differentiated Social Studies Learning - Chairani, Chairani; Elpisah, Elpisah; W, Muhammad Fahreza (CV. Rayyan Dwi Bharata, 2025)
This research aims to determine and describe the motivation of class VII students in implementing differentiated social studies learning at SMPN 13 Bontoa, Maros Regency. This type of research is descriptive research with a qualitative approach. The data source used is the primary data source. The subjects of this research were 3 class VII students at SMPN 13 Bontoa, Maros Regency with the criteria for high, medium and low learning motivation in differentiated social studies learning. Data collection techniques using questionnaires, observation and interviews. The data analysis technique used is the Miles and Huberman model. The results of this research show that students with high learning motivation criteria have high differentiated social studies learning motivation, this is seen based on the five motivation indicators, of which four meet the learning motivation variable. Then, based on the five indicators studied, students with medium and low learning motivation criteria only met one learning motivation variable. However, students with medium learning motivation criteria have higher differentiated social studies learning motivation than students with low criteria. This can be seen based on the items that medium criteria students do not always fulfill, namely 5 items, while low criteria students do not always fulfill 8 items out of a total of 13 items studied.